2022
DOI: 10.1007/s10461-022-03757-8
|View full text |Cite
|
Sign up to set email alerts
|

Influences on PrEP Uptake and Adherence Among South African Women During Periconception and Pregnancy: A Qualitative Analysis

Abstract: Pre-exposure prophylaxis (PrEP) is highly effective for HIV prevention, yet PrEP delivery to women in periconception and pregnancy has lagged. We report qualitative research from a study evaluating PrEP use as part of safer conception care for 330 South African women. Fifty-two semi-structured interviews were conducted with 25 study participants to identify influences on PrEP adherence. Influences were: (1) changing proximity to male partners; (2) COVID-19 lockdown; (3) mobile lifestyle; (4) PrEP-related stigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…16 FSW may also be worried about the potential impact on fertility or unborn children. 17 Evidence has shown that PrEP is safe, and it is not associated with any increased risk of severe adverse events. 18,19 Thus, messaging on PrEP to YKP, particularly FSW, should accurately address safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…16 FSW may also be worried about the potential impact on fertility or unborn children. 17 Evidence has shown that PrEP is safe, and it is not associated with any increased risk of severe adverse events. 18,19 Thus, messaging on PrEP to YKP, particularly FSW, should accurately address safety concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these studies have demonstrated that the pandemic has exacerbated existing barriers to care in these settings, including structural, clinical, and psychosocial barriers that affect access to perinatal pre-exposure prophylaxis (PrEP) and postexposure prophylaxis, HIV testing, and ART. [10][11][12][13] Public health measures implemented in March of 2020 in British Columbia (BC) included restrictions to mass gatherings, closure of various service establishments, and restriction to travel. 14 Such measures would have negatively affected peer support and social connection, which are critical adjunctive measures to clinical care for people living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these studies have demonstrated that the pandemic has exacerbated existing barriers to care in these settings, including structural, clinical, and psychosocial barriers that affect access to perinatal pre-exposure prophylaxis (PrEP) and postexposure prophylaxis, HIV testing, and ART. 10–13…”
Section: Introductionmentioning
confidence: 99%
“…Studies in other sub-Saharan African contexts have demonstrated feasibility regarding PrEP implementation in maternal and child health (MCH) clinic settings (19). However, recent South African studies have showed that PBFW currently face several barriers to accessing PrEP, such as anticipated and internalized stigma, lack of provider knowledge, and challenges in disclosure of PrEP use (20,21). Studies conducted across several different contexts have found that many health care providers (HCPs) describe their PrEP knowledge as insu cient, resulting in inaccurate patient education and HIV counselling, hesitancy to prescribe PrEP, and a lack of con dence in completing PrEP-related clinical activities (22,23).…”
Section: Introductionmentioning
confidence: 99%